THE EFFECTIVENESS OF THE IMPLEMENTATION OF THE CIVIL STATE APPARATUS INFORMATION SYSTEM AT THE PERSONNEL AND HUMAN RESOURCES DEVELOPMENT AGENCY OF BIAK NUMFOR REGENCY - Amiruddin, Amiruddin; Dasem, Ema E; Ghalib, La Ode Muhamad; Msen, Dominggus; Lopuhaa, Marlina; Arunglangi, Agustina; Sroyer, ⁠Simon F.; Kapisa, Absalom (Gema Kampus IISIP YAPIS Biak, 2025)
This study aims to analyze the effectiveness of the implementation of the Civil State Apparatus Information System (SIASN) at the Personnel and Human Resources Development Agency (BKPSDM) of Biak Numfor Regency. The research employs a qualitative descriptive approach, collecting data through interviews with BKPSDM officials, direct field observations, and documentation analysis. Results demonstrate that SIASN implementation has positively impacted the efficiency and accuracy of civil service administrative processes, including data management, rank promotions, mutations, and pension services. Based on effectiveness indicators—including program understanding, target accuracy, timeliness, goal achievement, and tangible change—the system is considered effective in supporting integrated ASN data governance at the national level. However, significant challenges persist, including internet connectivity issues in remote areas, server capacity constraints during peak usage periods, and limited user training beyond system administrators. The study identifies infrastructure improvements, expanded training programs, increased user support services, and data integration with national population systems as critical factors for enhancing SIASN effectiveness. These findings provide empirical evidence for policymakers and administrators in Biak Numfor and other regions on strengthening digital transformation in civil service administration.